Transcatheter mitral valve intervention: an emerging treatment for mitral regurgitation. Issue 4 (6th April 2018) - Markham, Ryan; Kyranis, Stephen; Aroney, Nicholas; Lau, Katherine; Poon, Karl; Scalia, Gregory; Walters, Darren
Abstract: Mitral regurgitation (MR) is a valvular heart disease associated with significant morbidity and mortality. Transcatheter mitral valve intervention (TMVI) repairs or replaces the mitral valve through small arterial and venous entry sites and so avoids risks associated with open heart surgery. Transcatheter devices targeting components of the mitral apparatus are being developed to repair or replace it. Numerous challenges remain including developing more adaptable devices and correction of multiple components of the mitral annulus to attain durable results. The mitral valve apparatus is a complex structure and understanding of the mechanisms of MR is essential in the development of TMVI. There will likely be a complementary role between surgery and TMVI in the near future.